2008
DOI: 10.1186/1745-0179-4-17
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge about childhood autism among health workers (KCAHW) questionnaire: description, reliability and internal consistency

Abstract: BackgroundKnowledge and awareness about childhood autism is low among health workers and the general community in Nigeria and other Sub-Saharan African countries. Poor knowledge and awareness about childhood autism, especially among health workers can compromise early recognition and interventions which had been known to improve prognosis in children with autism. In formulating policy and designing interventions for these children, there is need to develop a reliable tool that can be used in assessing baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
108
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(136 citation statements)
references
References 20 publications
6
108
2
1
Order By: Relevance
“…Participants with experience scored higher regarding their knowledge of childhood ASD than those who did not, which was consistent with prior research (8). Presumably, such experience could increase the understanding of children with ASD in general.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Participants with experience scored higher regarding their knowledge of childhood ASD than those who did not, which was consistent with prior research (8). Presumably, such experience could increase the understanding of children with ASD in general.…”
Section: Discussionsupporting
confidence: 86%
“…As previous research has shown (6,8), there were no significant associations among childhood ASD knowledge, age and work duration for healthcare workers. Those who are older and probably with more years of experience may not necessarily score higher on the knowledge of childhood ASD questionnaire.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Inadequate knowledge on these domains may lead to delayed identification and intervention. Previous studies demonstrate that the knowledge on co-morbidities of autism is especially poor 7,11 . This also holds true for our study, with 53% being unaware of the association of epilepsy with autism.…”
Section: Discussionmentioning
confidence: 99%
“…A specifically designed questionnaire for sociodemographic details and the "Knowledge about Childhood Autism among Health Workers (KCAHW) Questionnaire" were used. KCAHW questionnaire was developed in Nigeria, and is recommended for use in developing countries 7 .The questionnaire utilizes widely accepted symptoms of autism that are taught in medical schools in Sri Lanka in English. This has a total of nineteen questions divided into four domains; namely impairments in social interactions, impairment of communication and language development, restricted, repetitive and stereotyped behaviour and common associations of childhood autism.…”
Section: Methodsmentioning
confidence: 99%